The Existence Of PT Jamsostek In Social Security Services For Participant Time Working Agreements (PKWT) ( Study at PT Jamsostek (Persero) Belawan Branch) - Jones Parapat (Institute Of computer Science (IOCS), 2020)
One of the rights inherent in human nature and existence is the right to social security. Therefore it is often argued that social security is a universal/general program that must be implemented by all countries. In the 1948 United Nations Universal Declaration of Human Rights Article 22 and Article 25 it is stated that: